The Mediating Role of Theory of Mind in the Relationship Between Executive Functions and Marital Burnout Using Structural Equation Modeling and Artificial Neural Networks (SEM-ANN) - Babaei, Fatemeh; Abdollahi, Mohammadhossein; Amini Gilvani, Maryam; Masoomifard, Marjan (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the mediating role of theory of mind (ToM) in the relationship between executive dysfunction and marital burnout. Methods and Materials: The study employed a descriptive-correlational design with a sample of 300 married women from counseling centers in Tehran. Data were collected using the Barkley Deficits in Executive Functioning Scale, the Baron-Cohen Theory of Mind Questionnaire, and the Pines Couple Burnout Measure. To analyze the data, structural equation modeling (SEM) was used to examine the direct and indirect relationships between variables, and artificial neural networks (ANN) were employed to explore nonlinear and interactive effects. Findings: The results showed a significant positive relationship between executive dysfunction and marital burnout, as well as a significant negative relationship between ToM and marital burnout. Mediation analysis revealed that ToM partially mediated the relationship between executive dysfunction and marital burnout. Both SEM and ANN analyses confirmed the robustness of the relationships between executive functions, ToM, and marital burnout, with executive dysfunction emerging as the strongest predictor of marital burnout. Conclusion: The findings suggest that impairments in executive functions contribute to marital burnout both directly and indirectly by affecting ToM. Interventions aimed at improving executive functions and ToM, such as mindfulness-based programs and cognitive-behavioral therapies, may help reduce the risk of marital burnout. These results underscore the importance of cognitive and social processes in understanding and addressing relationship dissatisfaction and emotional exhaustion in marriages.